Pemanfaatan Teknologi dalam Pengelolaan Keuangan Santri Melalui Penggunaan Software Akuntansi dan Voucher Belanja di Pesantren - Rizal Fahlefi; Muhammad Deni Putra; Alimin Alimin; Widi Nopiardo (Jurnal Ilmiah Ekonomi Islam, 2022)
The problem that underlies this research is that at the Ulul Albab Modern Islamic Boarding School for Famales, Koto Baru, Dharmasraya Regency, West Sumatra Province, financial management is still manual and resources in the field of information technology are also lacking. Therefore, Ulul Albab uses financial applications to streamline the financial management of students and implements a shopping system using an integrated voucher application system. This study aims to explore the use of technology in the form of accounting software and shopping vouchers in managing the finances of students at Ulul Albab. The research uses the qualitative method and case study approach. The results showed that Ulul Albab utilizes existing technology to assist in the financial management of students. The "BENTAR" software is used and it is also integrated with the student shopping vouchers. The accounting staff of Ulul Albab are given training in operating the software so that they can use it according to its functions and benefits, while students are given training on the use of shopping vouchers so that they can use it according to their individual needs. The utilization of the technology is continuously monitored until it is believed that it can actually run well. This is an indicator of the ability of Ulul Albab to adapt to digitalization in the industrial era of 4.0. The transformation carried out by Ulul Albab can become a technology-based financial management model in Islamic boarding schools.